The Correlation Leadership Style and School Productivity - Mukhtar Mukhtar; Risnita Risnita; Dian Cita Sari (International Journal of Education, Information Technology, and Others, 2020)
The objectives of this study were to identify the levels of leadership style and to explore the relationship between headmaster’s leadership style and their School Productivity in Madrasah Aliyah 1 at Riau Province. Leadership style conceptual Framework was used as the framework to guide the study. The sample consisted of 30 respondent. The result from the mean percentages of leadership style levels obtained that among the leadership style dimensions, Data presentation showed the high level productivity. However, four dimensions such as productivity search skills, productivity retrieval skills, productivity interpretation skills and productivity management skills indicated moderate level among school productivity. Spearmen correlation presented that Productivity search skill has significant relationship to the School Productivity. However, data presentation skills, productivity retrieval skills, productivity interpretation skills and productivity management skills were not significant relationship to the School Productivity.